Optimized production of gamma poly glutamic acid (γ-PGA) using locally isolated Bacillus megaterium bacteria for potential application in some food products - Eman, J A A; Suzan, K Hasan; Luma, Khairy Hassan; Hanisah, Kamilah (Horizon E-Publishing Group, 2026)
Poly-γ-glutamic acid (γ-PGA) is a water-soluble amino acid biopolymer produced by bacterial fermentation. γ-PGA functioned as a precursor of protein development, including glutamate, an amino acid that provides an umami taste, especially in foods rich in proteins. Thus, in this study, the gamma polyglutamic acid (γ-PGA) obtained from genetically improved local isolate Bacillus megaterium was added to a few food products, and the quality changes of the foods were evaluated. Crude γ-PGA samples were produced from genetically modified locally isolated Bacillus megaterium biosynthesis. The bacteria culture medium (g/L) consists of 100 g glucose, 20 g ammonium nitrate, 2.5 g corn soaking liquid, 0.5 g MgSO4.7H2O, 0.01 g FeSO4.7H2O, and 0.005 g MnCl2.2H2O and is added with 3 % v/v of the bacteria culture. Then, sensory evaluation was conducted on three types of food products (mayonnaise, mushroom soup, and chicken sausage) after γ-PGA was added in different concentrations. The addition of γ-PGA was different for each food product based on the food standard concentrations: mayonnaise, 0.4 %, 0.7 % and 1 % respectively; chicken sausages, 0.2 %, 0.5 % and 0.8 % respectively and mushroom soup, 0.2 %, 0.25 % and 0.3 % respectively. Potato starch was tested on food products, respectively, as a comparison with a commercial thickener agent. The results showed that the sensory evaluation reported no significant differences (P > 0.05) with the samples that contained 2.5 % potato starch. The (γ-PGA) synthesized from genetically modified, locally isolated Bacillus megaterium improved the tested food products' texture, taste and palatability.